Enolase-specific cross antibodies induce neutrophilic inflammation in the intestine. Issue 3 (18th August 2020) - Lin, Jianli; Feng, Bai-Sui; Huang, Nana; Ma, Na; Liu, Zhi-Qiang; Shu, Qing; Zhong, Nanshan; Liu, Zhi-Gang; Yang, Ping-Chang
Abstract: The pathogenesis of ulcerative colitis (UC) is to be further investigated. House dust mites (HDM) are highly associated with the pathogenesis of immune inflammation in the body. This study aims to investigate the role of enolase (one of the HDM-derived proteins)-specific cross Abs in the induction of UC-like inflammation. The enolase specific IgG (EsIgG) was identified in UC patients by mass spectrometry. Mice were treated with EsIgG to induce inflammation in the colon mucosa. EsIgG was detected in the serum and the colon tissues of UC patients, which was positively correlated with the polymorphonuclear neutrophil (PMN) counts in the blood and colon tissues of UC patients. EsIgG formed immune complexes with the constitutive enolase in the UC colon epithelium that activated complement, induced epithelial cell apoptosis, compromised epithelial barrier functions, and resulted in UC-like inflammation in the mouse colon. In summary, UC patients have high serum levels of Abs against HDM-derived enolase and intestinal epithelial cell-derived enolase. These Abs attack the colonic epithelium to induce UC-like inflammation. Graphical Abstract: Mite-specific autoantibody-related neutrophilic infiltration plays a critical role in the pathogensis of IBD